Failure mechanisms and dynamic process control measures of deep buried tunnels in tectonic fracture zones under high in-situ stresses—a case study in Southwestern China - Zheng, Keyue; Shi, Chenghua; Zhao, Qianjin; Lei, Mingfeng; Jia, Chaojun; Lou, Yili (Frontiers in Earth Science, 2023)
With the development of railways in Southwestern China, there are more and more deep tunnels passing through the tectonic fracture zones under high in situ stresses, which easily causes large deformation during tunnel construction. This study is based on the project of the Wanhe tunnel of the China-Laos railway. First the failure mechanism was investigated through field testing including the in-situ stress, loosened zone, deformation monitoring, and internal stresses of steel arches. Then, this study proposed the dynamic process control method following the combination principle of stress releasing and support resistance. The dynamic process control measures were further proposed in this paper including the advanced and primary supports, the deep-shallow coupled delayed grouting method, and the double steel arches method. The results of this study indicate that the rapid growth of the tunnel deformation in the early stage was caused by the squeezing effect, and later the loosening effect led to another growing trend of the vault settlement.The dynamic process control method allows an appropriate amount of released deformation in the rapid growth stage and then requires to control the deformation within the reserved range by strengthening the rock or supports in the later stage. From the feedback of monitoring results, large deformation of Wanhe tunnel was well released and effectively controlled within the deformation allowance. Thus these countermeasures based on the dynamic process control method can guarantee the construction safety of deep tunnels in tectonic fracture zones under high in-situ stresses.